Quality of the service provided by Stay Hotel Lisboa Aeroporto: Analysis of online reviews and strategies for improvement - Leiria, Catarina Andrade dos Santos (2022)
Due to an increasing tourism offer, travelers look for memorable and unique experiences along the whole journey. Furthermore, the technology has been changing the game more than ever, and thus customer feedback, especially the online one, is shaping the whole industry. As such, to succeed and differentiate themselves in the current context, destinations and all organizations related to the tourism and hospitality industry must be able to deliver an outstanding service. In this context, the objective of the current project is to assess the quality of the service provided by Stay Hotel Lisboa Aeroporto, through the analysis of their online reviews on Booking.com with the Leximancer software. The aim consists of identifying the main themes in guests’ comments shared online and understand which aspects must be improved. This analysis will also be performed segmenting the comments by “rating given”, “room type”, and “traveler type”. Out of 1711 reviews analyzed, 12 general themes were identified: “staff”, “room”, “location”, “(value for) money”, “stay”, “night”, “service”, “everything”, “pleasant”, “noise”, “comfort” and “recommend”. Overall, gusts were satisfied with their experience at Stay Hotel Lisboa Aeroporto, as almost 60% gave the highest rating possible in their review, whereas only around 2% of the comments corresponded to the lowest ratings (2 and 1). Shortly, guests were pleased with the hotel’s staff, location, service, and value for money. However, several issues were identified in the online feedback provided by the reviewers, and it is recommended that the hotel addresses them in an appropriate way.